Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.